2020
DOI: 10.1016/j.idcr.2020.e00949
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a prosthetic hip infection due to Enterococcus faecalis with sequential dosing of oritavancin and prosthesis preservation without prosthetic joint surgical manipulation

Abstract: A patient with a prosthetic joint infection (PJI) complicated with deep surgical site infection due to vancomycin-susceptible Enterococcus faecalis. The initial treatment consisted of 10 days with daptomycin plus ampicillin. The hip prosthesis was retained and salvaged with six outpatient sequential doses of oritavancin 1200 mg every seven days without intra-articular irrigation or other surgical interventions. The patient was ambulating independently without symptoms after ten months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…According to our inclusion criteria, we selected 16 papers [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] for data extraction (see Supplementary Materials Table S1). They were all retrospective and most of them were case reports or case series (10/16; 62.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our inclusion criteria, we selected 16 papers [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] for data extraction (see Supplementary Materials Table S1). They were all retrospective and most of them were case reports or case series (10/16; 62.5%).…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus was the predominant pathogen with the highest success rate (81.5% MRSA, 75.0% MSSA), followed by CoNS (58.3%) and Enterococci. According to our inclusion criteria, we selected 16 papers [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] for data extraction (see Supplementary Materials Table S1). They were all retrospective and most of them were case reports or case series (10/16; 62.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Oritavancin has shown adequate in vitro bactericidal activity and sterilisation ability of biofilms, and some retrospective applications have described successful use in bone and prosthetic-associated infections as well [19,21,24,25], including one case with retained prosthetic materials [24]. In vitro studies have shown the ability of oritavancin to accumulate extensively in macrophages, potentially enhancing the eradication of pathogens that survive in lysosomes [1].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies [18,19,21] and case reports [22][23][24][25] describing off-label use in bone and prosthetic-associated infections. A multicentre retrospective study described 134 patients with acute osteomyelitis who obtained clinical success in 88.1% of cases-defined as the resolution of symptoms or improvement of symptoms and no further need for treatment-after receiving four or five doses of oritavancin (1200 mg, then 800 mg weekly).…”
Section: Oritavancin In Bone and Prosthetic Joint Infectionsmentioning
confidence: 99%
See 1 more Smart Citation